The Effect of Mathematical Logical Intelligence, Mathematical Connections, and Learning Interest on Students' Mathematical Problem Solving Ability - Sabiila, Aziizun; Susongko, Purwo; Munadi, Munadi (Journal of English Language and Education, 2025)
Mathematical problem solving is a high-level thinking skill that needs to be developed in mathematics learning. However, there is a gap in the integration of logical-mathematical intelligence, mathematical connections, and learning interests holistically, because learning tends to focus more on memorization than contextual problem solving. This study aims to analyze the influence of logical-mathematical intelligence, mathematical connection ability, and learning interests on students' mathematical problem solving abilities. This study uses a quantitative method with data analysis techniques using SPSS 23. The research locations include SD Negeri Bojong 01, SD Negeri Bojong 02, and SD Negeri Bojong 03 in Bojong District, Tegal Regency, with a population of all grade IV students and a sample of 124 respondents. The results of the study indicate that: (1) there is a significant influence between logical-mathematical intelligence and students' mathematical problem solving abilities; (2) there is a significant influence between mathematical connection ability and students' mathematical problem solving abilities; (3) there is a significant influence between learning interests and students' mathematical problem solving abilities; and (4) there is a significant simultaneous influence between logical-mathematical intelligence, mathematical connection ability, and learning interests on students' mathematical problem solving abilities. These findings emphasize the importance of a holistic approach in mathematics learning to improve students' problem-solving abilities.